Assessing user acceptance towards virtual museum: The case in Kedah State Museum, Malaysia - Awang, Norazimah; Yaakub, Abdul Razak; Othman, Zakirah (IEEE, 2009)
This paper describes the testing analysis that has been done towards a prototype of virtual museum named ViSeum. The prototype was based on the real Kedah State Museum (KSM) at Northern Malaysia. This ViSeum was developed using non immersive virtual reality technique,whereas it focused to reduce cost development and maintenance, easy access and more interactive. The objective of this study is to present the result of the analysis based using Technology Acceptance Model on the survey.Perceived usefulness, perceive ease of use, and perceived enjoyment are the independent variables in testing intention to use by visitor.